FIKIH LINGKUNGAN DALAM PETA PEMBANGUNAN NASIONAL - Andi Yaqub (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
Conservation of the environment is a form or mode of managementand protection of all things related to human life wisely andsustainably. Understanding of the environment is closely related to therealization of the ideals of the nation and the country. Therefore, theprojection of understanding is arranged in the national developmentmap. One of the ideal perspective is the deep understanding of theenvironment and the philosophy of the nation of Islamicjurisprudence/islamic law.Beginning the concept of environmental conservation focuses on thelove of nature as a manifestation of servantship to Allah swt. Theteleological review positioned the approach of environmentaljurisprudence as the ideal framework for environmental conservation.The substance of jurisprudence / Islamic law emphasizes the paradigmof goodness that delivers individual consciousness and socialconsciousness.Environmental jurisprudence can be contained in the law substance, inthe Law as well as government regulations, whether located at thecenter, and at the region. The implementation phase also positions thestrengthening of Islamic law as an ethical approach and also as a socialcontrol. The rules on environmental conservation in Indonesia arecategorized under environmental law, environmental science andenvironmental politics.